Costs and returns of Saludan and Sungkit fishing methods in the schrimp (acetes spp) fishery of Tigbauan, Iloilo. - Marolina, Michelle Amor.; Tampos, Yoko S. (2003.)
The study determined and analyzed the economic profitability of saludan and sungkit fishing methods employed by the municipal fishers in Tigbauan. Specifically, the study described the socio-economic characteristics of the owners/owner-operators of saludan and sungkit, determined their costs incurred and revenues earned, and identified the problems encountered in fishing., The primary data were mainly gathered from the 33 owners/owner-operators of saludan and sungkit in Tigbauan who comprised the study population. They came from coastal barangays in Tigbauan who comprised the study population. They came from coastal barangays in Tigbauan, which were actively using saludan and/or sungkit fishing methods. Those barangays were BarangayBarroc, Atabayan, Baguingin, Namocon, and Tanpael. An interview schedule was used to gather data. Utilizing costs and returns analysis, results showed that both saludan and sungkit respondents earned positive pure economic profit. Sungkit respondents received and amount of P 1,369.34 per trip, which was much higher than the pure economic profit of P 103.76 per trip received by saludan respondents. The problems encountered by saludan and sungkit respondents include bad weather, strict implementation of territorial boundaries, limited fishing area, high expenses incurred, low prices, and problems with laborers.
Thesis (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Saludan Fishing Methods -- Tigbauan, Iloilo; Sungkit Fishing Methods -- Tigbauan, Iloilo